2013
DOI: 10.1080/19443994.2013.792164
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of cotton printing and dyeing wastewater by supercritical water oxidation

Abstract: A B S T R A C TThe cotton printing and dyeing wastewater obtained from a printing and dyeing mill was treated by supercritical water oxidation (SCWO) in a continuous-flow reactor. The experiments were operated between 400 and 600˚C, 25 MPa was selected as a suitable pressure, hydrogen peroxide (H 2 O 2 ) was used as an oxygen source, and excess oxygen varied from 0 to 300%. The studies indicate that the total organic carbon (TOC) degradation efficiency is over 99.7% when the temperature increases to 600˚C at 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In addition, disodium terephthalate (TADS), a characteristic pollutant of alkali reduction wastewater, can change into terephthalic acid (TPA) by acidifying with sulfuric acid. 2,3 TPA is a crucial industrial raw chemical that is extensively utilized in the food, cosmetics, and unsaturated polyester resin sectors. It had been reported that the hydrolytic precipitation of TPA from alkali reduction wastewater can be realized via the regulation of pH with sulfuric acid.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In addition, disodium terephthalate (TADS), a characteristic pollutant of alkali reduction wastewater, can change into terephthalic acid (TPA) by acidifying with sulfuric acid. 2,3 TPA is a crucial industrial raw chemical that is extensively utilized in the food, cosmetics, and unsaturated polyester resin sectors. It had been reported that the hydrolytic precipitation of TPA from alkali reduction wastewater can be realized via the regulation of pH with sulfuric acid.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Chemical treatment technology can reach better performance: 70% at the price of higher investment and operating cost. Physical adsorption technology, the most effective wastewater treatment method, mainly use adsorption characteristics of porous substance to filter out organic dye -stuffs, and the removal rates of color has been reported more than 90% [3][4][5][6][7]. Therefore, for wastewater-treatment industry, the choice of more economical and efficient adsorbents and the study of their adsorption are the contemporary focusing issue.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of social and the improvement of living standards, the people ask for the increasing quality of textile. Textile and garment industry is under ongoing technological innovation to meet different market needs, so that printing and dyeing wastewater is more and more different to treat [1][2][3] . However, with the chemical coagulation help, it can reduces chroma, turbidity and COD of the wastewater in the maximum extent [4] .…”
Section: Introductionmentioning
confidence: 99%